Penerapan Layanan Bimbingan Kelompok dalam Membentuk Konsep Diri Positif Siswa Pengguna Media Sosial - Gebitson Allo Layuk; Kartika Bato Kendek; Win Tasik (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This research aims to examine the implementation of group guidance services in developing a positive self-concept among students who actively use social media. The rapid development of digital technology has positioned social media as a space for self-expression, yet uncontrolled use often leads to negative social comparisons that distort adolescents' self-perception. This study employed a qualitative approach with a descriptive design. Data were collected through deep interviews, observations, and documentation involving students at IAKN Toraja. The findings indicate that group guidance services, conducted through the stages of formation, transition, core activity, and termination, significantly contribute to the formation of a positive self-concept. There is a notable improvement in students' self-confidence, self-acceptance, and self-control regarding social media usage. The group dynamics provide a supportive social laboratory for students to share experiences and receive constructive feedback, allowing them to reconstruct a more realistic and healthy self-image. The implication of this study suggests that group guidance can be an effective intervention for school counselors to mitigate the negative psychological impacts of digital interaction and foster digital literacy among students.